1994
DOI: 10.1038/bjc.1994.34
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study with subcutaneous low-dose interleukin 2 alone vs interleukin 2 plus the pineal neurohormone melatonin in advanced solid neoplasms other than renal cancer and melanoma

Abstract: Summary Our previous experimental studies have shown that the best approach to increase the biological anti-tumour activity of interleukin 2 (IL-2) is not co-administration of another cytokine, but the association with immunomodulating neurohormones, in an attempt to reproduce the physiological links between psychoendocrine and immune systems, which play a fundamental role in the regulation of the immune responses. In particular, the association with the pineal neurohormone melatonin (MLT) has been shown to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 12 publications
2
50
0
4
Order By: Relevance
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32,33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32,33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin also seems to boost the anti-tumor activities of IL-2 in humans with solid neoplasms [80].…”
mentioning
confidence: 99%
“…Previous studies (Bubenik and Purtill, 1980;Wiechmann and O'Steen, 1992;Sugawara et al, 1998) have suggested a potential detrimental effect of melatonin on photoreceptor cell survival in albino rats, and many reports suggest that melatonin may be beneficial for combating cancer, Lissoni et al, 1994), alleviating jet lag (Claustrat et al, 1992;Petrie et al, 1989) and entraining circadian rhythms (Petrie et al, 1989;Armstrong, 1989) such as sleep patterns (Reiter, 1980;Dollins et al, 1994). These perceived benefits have motivated many Americans to self-administer melatonin.…”
Section: Discussionmentioning
confidence: 99%